Ave, llena de gracia, el Señor es contigo" (Lc 1,28) En la interpretación de los Padres de la Iglesia (2016)
The words of the angelic salutation, which we read in the Gospel of Luke, have been the object of Christians’ reflections since the beginning of the Church and consequently have influenced the spirituality of the whole subsequent history of Christianity. Luke's expression appears in the form of graphite, in the third century in the primitive Basilica of Nazareth (Briand, 1987 p 26); also in the oldest of the frescoes, located in the catacombs of St. Priscilla in Rome (Quacquarelli & Bisconti, 1899 pp 255-256), dating back to the third century, while the same subject then covers the mosaics of the Basilica Santa Maria Maggiore in Rome, which dates back to the fifth century These words have inspired artists of a multitude of paintings and infinite musical works, expressed over a period of two thousand years.